THE ROLE OF ACCOUNTANTS, INTEGRATION OF ARTIFICIAL INTELLIGENCE (AI) AND INTERNET OF THINGS (IoT) IN FACING ECONOMIC DIGITALIZATION AHEAD OF THE SOCIETY 5.0 ERA - Resty Dwi Septiyanti; Eva Wany Wany; Budi Prayitno (Income, 2025)
The development of information and communication technology, especially through the integration of Artificial Intelligence (AI) and Internet of Things (IoT) innovations, has had a major impact on many sectors, including the world of accounting. Economic digitalization, which is part of the preparations towards Society 5.0, requires the accounting profession to adapt to various new technologies that can increase efficiency and accuracy in the accounting process. This research aims to explore the role of accountants in facing the digital era and Society 5.0 and examine how the integration of AI and IoT can be applied in accounting practice. The method used is a qualitative method with a literature study approach and interviews with accounting practitioners and technology experts. The research results show that accountants need to increase their competence in understanding and utilizing AI and IoT to optimize accounting performance and provide added value in the organization. In facing Society 5.0, accountants are expected to become agents of change who not only manage financial information, but can also manage big data and new technology to create smarter and data-based decisions.